Human capital formation: History, expectations, and challenges in South Africa - Yamauchi, Futoshi (International Food Policy Research Institute, 2010)
The end of the apartheid system in South Africa in 1994 brought with it the end of legally sanctioned racial segregation in schools. In practice, however, racial disparities in educational attainment continue, with white and Asian students outperforming the country's African majority in school. Such a gap in achievement has a significant impact on the ability of Africans to get jobs and escape poverty. Human Capital Formation: History, Expectations, and Challenges in South Africa investigates the causes of South Africa's persistent schooling imbalances, examining education laws and policies, as well as other influences on human capital investment. The study finds that inaccessibility of quality education, resulting from a lack of financial resources at both the local and household levels, is currently a significant constraint on educational attainment among the poor. This limitation will likely relax in the future as the government continues to subsidize schools, but the study also concludes that educational disparities cannot be overcome by direct attention to schools alone. For example, children require adequate nutrition at the pre-school stage in order to perform well in school. Furthermore, parental death or illness resulting from the HIV/AIDS epidemic can disrupt the education of adolescents, who might need to leave school to care for their parents or support their family. Steps to compensate for these problems, as well as improved access to schools, are necessary. These findings clarify the problems underlying inequalities in educational attainment, offering guidance to policymakers, development specialists, and others concerned with South Africa's welfare.